The methods of study of physico-mechanical characteristics of polyurethane binder of the system Cold-box-am - D. M. Kukuj; D. A. Kudin (Литьë и металлургия)
The offered procedure can be used for control of physical-mechanical characteristics of polyurethane cover. The received results can be interpreted from the viewpoint of specification of the fastness forming mechanism of the slugs of Cold-box-amin system.